An fMRI study of joint action–varying levels of cooperation correlates with activity in control networks - Chaminade, Thierry; Marchant, Jennifer L.; Kilner, James; Frith, Christopher D. (Frontiers in Human Neuroscience, 2012)
As social agents, humans continuously interact with with the people around them. Here, motor cooperation was investigated by designing a situation in which pairs of participants, one being scanned with fMRI, controlled jointly a visually presented object with joystick movements. The object oscillated dynamically along two dimensions, shades of pink and width of gratings, corresponding to the two cardinal directions of joystick movements. While the overall control of each participant on the object was kept constant, the amount of cooperation along the two dimensions varied along four levels, from no (each participant controlled exclusively one dimension) to full (each participant controlled half of each dimension) cooperation. Increasing cooperation correlated with BOLD signal in the left parietal operculum and anterior cingulate cortex, while decreasing cooperation correlated with activity in the right inferior frontal and superior temporal gyri, in the intraparietal sulci and inferior temporal gyrii bilaterally, and in the dorsomedial prefrontal cortex. As joint control improved with the level of cooperation, we assessed the brain responses correlating with joint performance, and found that activity in most of the areas associated with levels of cooperation also correlated with the joint performance. The only brain area found exclusively in the negative correlation with cooperation was within the posterior region of the rostral medial frontal cortex, involved in the monitoring of action outcome. We therefore propose that this region responds to the predictability of visual feedback given the motor commands, which is maximal when participants do not cooperate as they fully control one dimension. Our results therefore indicate that, in the current experimental paradigm, the level of cooperation affects sensorimotor processing, but not mentalizing. Altogether, humans do not need to have access to others’ intentional states to cooperate on a joint motor control task.